Gamma radiation effects on diamond field-effect biosensors with fibroblasts and extracellular matrix - Krátká, Marie; Čermák, Jan; Vachelová, Jana; Davídková, Marie; Romanyuk, Nataliya; Kromka, Alexander; Rezek, Bohuslav (Colloids and surfaces. B, Biointerfaces, 2021)
Due to high biocompatibility, miniaturization, optical transparency and low production cost together with high radiation hardness the diamond-based sensors are considered promising for radiation medicine and biomedicine in general. Here we present detection of fibroblast cell culture properties by nanocrystalline diamond solution-gated field-effect transistors (SG-FET), including effects of gamma irradiation. We show that blank nanocrystalline diamond field-effect biosensors are stable at least up to 300 Gy of γ irradiation. On the other hand, gate current of the diamond SG-FET biosensors with fibroblastic cells increases exponentially over an order of magnitude with increasing radiation dose. Extracellular matrix (ECM) formation is also detected and analyzed by correlation of electronic sensor data with optical, atomic force, fluorescence, and scanning electron microscopies.
Keywords: Biosensors; fibroblasty; Fibroblasts; extracelulární matrix; Extracellular Matrix; Proteins; mikroskopie elektronová rastrovací; Diamond; Microscopy, Electron, Scanning; Diamond thin films; Field-effect transistors; Gamma irradiation; diamant; Biosensing Techniques; Atomic force microscopy; biosenzitivní techniky; Cells